Morfoanatomia e histoquímica de sementes em desenvolvimento de Euterpe oleracea Mart. (Arecaceae) - Pereira, João Alves Ferreira (2017)
The objective of this study was to characterize anatomically and histochemically the egg, the development stages of seeds, endosperm and the embryo of the Euterpe oleracea Mart. Flowers was collected before and after fertilization, fruits were collected at different stages of development, according to seed diameter and some morphological parameters: pericarp color and seed resistance against the cut of a stiletto blade. The biologic material were collected at Taíba, a district of São Gonçalo do Amarante - CE. All the different stages of floral bud and seeds were submitted to a histological and histochemical analysis through light microscopy. During the anatomical analysis it was possible to identify and classify the different structures namely: The ovule is hemianotropic, with differentiation only in the region of the micropyle. The outer tegument is thicker than the inner one and the placentation is of the axillary type with presence of paquicalaza, besides the presence of vascular bundles throughout the region of the external tegument. In the initial development the açaí endosperm is of the nuclear type becoming with the passage of its cellular development, with thickening of the cellular wall, rich in primary scores, formed by multidimensional cells and multiform and large in relation to the cells of the integument, the embryonic development is onagráceo or cruciferous type with the embryo stages of development: proembryo, globular, lateral heart and torpedo. During development the mature embryo has a small and conical shape; with two distinct parts: distal (haustory) and proximal (cotyledonary petiole) which holds an oblique meristem, an undifferentiated root axis and the apical axis imersed in the cotyledonary cavity. Histochemical analysis of the slides allowed to identify: The proximal region is rich in idioblasts containing rafides and phenolic compounds. Starch was evidenced by black color near the meristem regions. Lipids in orange color, Proteins in red, Pectins and Reserve Polysaccharides from Cell Wall in purple, these are reserve molecules in the endosperm of this specie. This is the first detailed study that describes the egg structures of the zygote embryo as well as the formation and development of Euterpe oleracea Mart endosperm. This study provides background subsidies for future studies in the areas of reproductive biology, Anatomy, plant morphology, biochemistry and various areas of agronomy as seed technology. This study of reproductive biology, anatomy and plant morphology, biochemistry and various areas of agronomy as seed technology.